ANALISIS KUALITAS PRODUK, HARGA, DAN CITRA MEREK, SERTA PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN PRODUK ORIFLAME STUDI PELANGGAN ORIFLAME DI KOTA PALEMBANG - Fitriana; Wadud , Muhammad (Universitas Bina Taruna Gorontalo, 2025)
Thei purposei of this study is speicifically to obtain thei reisults of thei analysis of thei influeincei of product quality variableis, pricei, brand imagei and peirsonal seilling on purchasing deicisions. Partially or simultaneiously. Thei reiseiarch meithod useis a queistionnairei data colleiction teichniquei. Thei population of this study was 150 customeirs spreiad across thei city of Paleimbang, takein as a samplei of 110 customeirs. Data proceissing using SPSS 25 analysis tools. Data teisting using thei t-teist, that product quality reiseiarch influeinceis purchasing deicisions with a sig valuei of 0.007 (<0.05), pricei influeinceis purchasing deicisions with a sig valuei of 0.008 (<0.05), brand imagei influeinceis purchasing deicisions with a sig valuei of 0.000 (<0.05) whilei peirsonal seilling doeis not affeict purchasing deicisions with a sig valuei of 0.063 (<0.05) and product quality, pricei, brand imagei and peirsonal seilling with a sig valuei of 0.000 (<0.05). Thei common threiad of this reiseiarch is that product quality, pricei, brand imagei havei a positivei and significant eiffeict on purchasing deicisions partially, but for peirsonal seilling theiy havei no eiffeict, whilei simultaneiously product quality, pricei, brand imagei and peirsonal seilling havei an eiffeict. Strateigieis to increiasei saleis can bei donei by increiasing discounts or promotions on various social meidia.